Peran dan Fungsi Humas dalam Publikasi pada Kantor Dinas Kelautan dan Perikanan Provinsi Sulawesi Selatan - Mahmud Mahmud; Fatmawati Fatmawati; Ismail Ismail (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
The success of government publications to the public cannot be separated from the role of public relations (public relations). Public relations or better known as PR (Public Relations) has a very large role and is very much needed by leaders. "Publication is very important, because then the public will know what the leaders or regional heads are doing. If there is no publication, it is as if the regional head is not working even though he has worked hard. This study aims to find out the role and function of Public Relations in Publication at the South Sulawesi Provincial Marine and Fisheries Office. This study uses a qualitative method with a qualitative descriptive approach, the data collection technique is through observation, interviews and documentation. while the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study show that one of the roles of public relations at the South Sulawesi Provincial Marine and Fisheries Office is to make publications about the activities of the South Sulawesi Provincial Marine and Fisheries Office which have an impact on how to create a good image for OPD (Regional Apparatus Organizations). these publication activities are published through social media, print media or electronic media. The social media used include Facebook, Instagram, YouTube, but it is still in personal content, not on the official website of the South Sulawesi Provincial Marine and Fisheries Service. Later, after being thrown to the public, it will be entered into the official website of the South Sulawesi Provincial Marine and Fisheries Service. The function of public relations in the South Sulawesi Provincial Marine and Fisheries Service is how to provide information to the public or community, in other words, how to invite other Regional Apparatus Organizations to popularize news about the South Sulawesi Provincial Marine and Fisheries Service, especially the South Sulawesi Provincial Marine and Fisheries Service.